Decreased expression of miR-146a and miR-155 contributes to an abnormal Treg phenotype in patients with rheumatoid arthritis. Issue 6 (21st February 2014) - Zhou, Qihui; Haupt, Sonja; Kreuzer, Johannes T; Hammitzsch, Ariane; Proft, Fabian; Neumann, Carla; Leipe, Jan; Witt, Matthias; Schulze-Koops, Hendrik; Skapenko, Alla
Abstract : Objectives: MicroRNAs (miRNAs) have been implicated in the pathogenesis of autoimmune diseases, not least for their critical role in the regulation of regulatory T cell (Treg) function. Deregulated expression of miR-146a and miR-155 has been associated with rheumatoid arthritis (RA). We therefore investigated miR-146a and miR-155 expression in Tregs of patients with RA and their possible impact on Treg function and disease activity. Methods: Expression of miR-146a and miR-155 was assessed in RA patients and controls. MiRNA expression was correlated with disease activity and expression of target genes. Interference with biological activity of miRNAs was evaluated in functional Treg assays. Results: Diminished upregulation of miR-146a and miR-155 in response to T cell stimulation was found in Tregs of RA patients. Diminution of miR-146a expression was observed in particular in patients with active disease, and correlated with joint inflammation. In patients with active RA, Tregs demonstrated a pro-inflammatory phenotype characterised by inflammatory cytokine expression. This was due to an augmented expression and activation of signal transducer and activator transcription 1 (STAT1), a direct target of miR-146a. Conclusions: Our results suggest that in RA miR-146a facilitates a pro-inflammatory phenotype of Tregs via increased STAT1 activation, and contributes thereby to RA pathogenesis.